Characterization of hemicelluloses in Phyllostachys edulis (moso bamboo) culm during xylogenesis. (1st October 2019) - Wang, Kai-li; Wang, Bo; Hu, Ruibo; Zhao, Xianhai; Li, Huiling; Zhou, Gongke; Song, Lili; Wu, Ai-min
Highlights: Hemicellulose in P. edulis was glucuronoarabinoxylans with side chain arabinose, glucuronic acid and acetylation. P. edulis xylan has no tetrasaccharides. Hemicellulose from apical to basal stem samples showed longer molecular weights. Acetyl substitutions of xylan are increased during the xylogenesis. Abstract: Hemicelluloses are β -(1→4)-linked backbone polysaccharides found in plant cell walls that include xyloglucans, xylans, mannans and glucomannans, and play important roles in plant tissue configuration. In this study, hemicelluloses were isolated from the apical, middle and basal segments of 6 m Phyllostachys edulis culm using KOH and DMSO extraction procedures, respectively. Chemical composition and structural characterization of hemicellulosic fractions were comparatively investigated by a combination of HPLC, GPC, FT-IR, 1 H-, 13 C-, HSQC NMR and TGA techniques. Our results show that the main chain of hemicellulose in P. edulis consists of glucuronoarabinoxylans (GAXs) with backbone 1, 4- β -d -Xyl, and side chain arabinose, glucuronic acid and acetylation. Hemicellulose content and molecular weight increased with culm xylogenesis in P. edulis . Our results provide new insights on the dynamics of hemicellulose structure in culm xylogenesis in P. edulis .